RANCANG BANGUN GAME ONLINE “WADAI 41” DENGAN ADOBE FLASH - Wahyu Ridhoni; Inayatul Ulya Ahyati (Program Studi Teknik Informatika, Politeknik Hasnur, 2016)
The objective of this research is designing and developing an online game about Wadai 41. It is the traditional cake from Kalimantan Selatan. But Nowadays all kinds of cultural relics is considered old-fashioned and not as exciting new culture characterized by technology trends. Concerns occur where young people are more interested in gadgets and began indifferent to cultural heritage. This fact led to the need for cultural content packaged in a way that utilizes newer technology. Game is a technology products that is entertaining. This media is very close to young people , so it is suitable to deliver content with teenagers segmentation. The result of this research is wadai 41 can be designed to be an online game. The development uses Adobe Flash that connected with MySQL database throught PHP. Keywords: Game, Wadai 41, Traditional Cake, Kalimantan Selatan, Adobe Flash